2018
DOI: 10.3390/nu10101430
|View full text |Cite
|
Sign up to set email alerts
|

Welsh Onion Root (Allium fistulosum) Restores Ovarian Functions from Letrozole Induced-Polycystic Ovary Syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is an endocrine, metabolic, and systemic disease. It is mainly characterized by hyperandrogenism, oligomenorrhea, and high levels of luteinizing hormone (LH). There is no obvious therapy for PCOS, so patients have received symptomatic therapy. Welsh onion (Allium fistulosum) is well-known in Asian countries for its usage in food ingredients and traditional medicines. It is also studied for its many effects. These include activation of immune responses, antihypertensive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 31 publications
13
36
0
Order By: Relevance
“…Our findings unveiled a significant downregulation of CYP19α1 mRNA expression level in PCOS ovary tissues. These results were consistent with previously published data (45,53,54). Remarkably, the AR and vit C combo showed superior and significant gene upregulation versus its components.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings unveiled a significant downregulation of CYP19α1 mRNA expression level in PCOS ovary tissues. These results were consistent with previously published data (45,53,54). Remarkably, the AR and vit C combo showed superior and significant gene upregulation versus its components.…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of LTZ rat model in the induction of PCOS is well established and represents human PCOS in various aspects (44)(45)(46). Oxidative stress may be engaged in the pathogenesis of PCOS (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 92%
“…Thus, numerous studies attempted to guide the development of new and effective therapies for PCOS. Recently, treatment based on traditional Chinese medicine and food ingredients, such as AF extract, soy isoflavones and crocetin, provided a novel therapeutic way for PCOS [22][23][24]. All these observations suggested rooms for improvement in PCOS therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has ability to activate the immune response and antihypertensive effect as well as antioxidant defense system. The consumption of A. fistulosum extract increased estrogen level, mediated the conversion of testosterone to estrogen, and conducted hormone balance in female rats resulting in the enhancement of ovarian function [74]. The extract is able to downregulate the accumulation of lipid in HepG2 cells without cytotoxic effect and fatty acid gene synthesis.…”
Section: Allii Fistulosi Bulbusmentioning
confidence: 95%